Basal follicle stimulating hormone and leptin on the day of hCG administration predict successful fertilization in in vitro fertilization (Faculty of Medicine Universitas Indonesia, 2016)
Background: Successful pregnancy in in vitro fertilization (IVF) program depends on multiple factors. This study aimed to determine whether age, body mass index (BMI), basal follicle stimulating hormone (FSH), estradiol, and leptin on the day of trigger ovulation with human chorionic gonadotropin (hCG) might be used as predictor for successful oocyte fertilization in in vitro fertilization (IVF) program. Methods: This is a cross sectional study conducted in Yasmin Fertility Clinic, Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Forty participating patients underwent IVF program, excluding smokers, patients with diabetic, morbid obesity, and severe oligospermia or azoospermia. Age, BMI, basal FSH, estradiol, leptin on the day of hCG administration, oocyte count on oocyte retrieval, the number of mature oocyte, and fertility rate were analyzed using bivariate and multivariate analysis to determine which eligible factors play role in predicting the successful of fertilization. Results: Significant correlation was found between basal FSH level and serum leptin/oocyte ratio on the day of hCG administration with successful fertilization. We found probability formula as follows: 1/(1+exp –(6.2 - 0.4(leptin serum/oocyte ratio) - 0.8(basal FSH)), with 77.8% sensitivity, 77.8% specificity, and AUC levels of 85.6% indicating strong predictability. Probability of successful fertilization related to basal FSH level of 5.90 mIU/mL and leptin serum/oocyte ratio of 3.98. Conclusion: The formula consisting of basal FSH and leptin serum/oocyte ratio on the day of trigger ovulation was capable in predicting the probability of successful fertilization in IVF procedure.